Regional division of the Republic of Macedonia for the needs of biological databases - Melovski, Ljupčo; Markovski, Blagoja; Hristovski, Slavcho; Jovanovska, Daniela; Anastasovski, Vasil; Klincharov, Sokol; Velevski, Metodija; Velkovski, Nikolcho; Trendafilov, Aleksandar; Matevski, Vlado; Kostadinovski, Mitko; Karadelev, Mitko; et al. (Macedonian Journal of Ecology and Environment, 2013)
The aim of the presented work is elaboration of consistent and geographically defined territorial division of the Republic of Macedonia that will serve to define floral, faunal and fungal distribution ranges. The main reason behind this is the need to harmonize biodiversity distribution data which are inconsistent due to the various understandings of the mountains’ and valleys’ territories and their borders in Macedonia of historic and current researchers. The regional division in the sense of this work means precise definition of the territories of the mountains, valleys, plateaus, river gorges and traditionally accepted regions (by the local population) in the Republic of Macedonia. Administrative division and other political-economic development regions were not considered. Basic criteria for this division were: geomorphology, traditional view of the spatial units, ecological, land use and biogeographic criteria. The use of toponyms, English quotation and spelling were harmonized as well. Ninety three individual regions were identified. Eight regions comprise additional 21 sub-regions which makes 106 spatial units in total. Out of them, 44 regions are mountainous, nine are hilly, two are plateaus, 22 are valleys or plains, six are river gorges, three are lakes and seven are traditionally known provinces.